2021
DOI: 10.1038/s42003-021-02227-6
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of candidate causal genes for asthma in susceptibility loci derived from UK Biobank

Abstract: To identify candidate causal genes of asthma, we performed a genome-wide association study (GWAS) in UK Biobank on a broad asthma definition (n = 56,167 asthma cases and 352,255 controls). We then carried out functional mapping through transcriptome-wide association studies (TWAS) and Mendelian randomization in lung (n = 1,038) and blood (n = 31,684) tissues. The GWAS reveals 72 asthma-associated loci from 116 independent significant variants (PGWAS < 5.0E-8). The most significant lung TWAS gene on 17q12-q2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 61 publications
(85 reference statements)
1
65
0
Order By: Relevance
“…Another possibility for our unique nasal findings regards differences in statistical power between the nasal and lung analyses, since the GTEx v7 lung sample size was 383 vs. the 681 nasal samples we analyzed. To evaluate this, we compared our nasal TWAS results to a recently published lung/UK Biobank-asthma TWAS 41 , 42 , which used a larger set of 1038 lung donors and >400,000 subject GWAS. This analysis only identified 55 asthma TWAS genes, with only 1 of the 11 AOA and 3 of 51 COA nasal-specific TWAS genes we identified among them.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility for our unique nasal findings regards differences in statistical power between the nasal and lung analyses, since the GTEx v7 lung sample size was 383 vs. the 681 nasal samples we analyzed. To evaluate this, we compared our nasal TWAS results to a recently published lung/UK Biobank-asthma TWAS 41 , 42 , which used a larger set of 1038 lung donors and >400,000 subject GWAS. This analysis only identified 55 asthma TWAS genes, with only 1 of the 11 AOA and 3 of 51 COA nasal-specific TWAS genes we identified among them.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining replicated CNVs, two affect genes also residing in the HLA: a partial deletion of the large, central exon of MUC22 , and a small deletion within the 3’UTR of TAP2 . Genetic variants in the MUC22 gene region [ 21 , 22 ] and in TAP2 [ 2 ] have been previously associated with asthma and asthma-related traits. The final two asthma-associated CNVs are partial gene duplications on chromosome 2 (affecting exons 4–8 of the PRKRA gene and the 3’ end of the CHROMR long non-coding RNA gene) and chromosome 12 (affecting exon 2 of the FBRSL1 gene).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the HLA-DQ locus was the first genetic locus to be associated with asthma [ 26 ]. Since then, many genetic studies have identified multiple, independent associations between HLA genes and susceptibility to asthma [ 2 , 18 , 20 , 27 29 ], as well as asthma subtypes [ 17 , 19 , 30 , 31 ] and related traits such as serum IgE levels [ 32 , 33 ]. Our fine-mapping analysis suggest that there are at least two independent genetic risk loci for asthma within the HLA region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc finger E-box binding homeobox 1 (ZEB1), an epithelial-mesenchymal transition (EMT) key regulator, has been reported involved in the airway smooth muscle cell proliferation 39 and nickel exposure-induced impairment of human lung epithelial cells 40 . Through transcriptome-wide association studies, transcription factor RERE was identified as a candidate causal gene of asthma 41 . The whole-genome expression analysis of peripheral blood mononuclear cells indicated that FOSL1 was positively associated with aspirin-intolerant asthma 42 .…”
Section: Discussionmentioning
confidence: 99%